Fatigue-free behavior of Bi3.25La0.75Ti3O12 thin films grown on several bottom eletrodes by the polymeric precursor method - Simoes, A. Z.; Ries, A.; Filho, F. M.; Riccardi, C. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2004)
Fatigue-free Bi3.25La0.75Ti3O12 (BLT) thin films were grown on LaNiO3,RuO2, and La0.5Sr0.5CoO3 bottom electrodes in a microwave furnace at 700 degreesC for 10 min. The remanent polarization (P-r) and the drive voltage (V-c) were in the range of 11-23 muC/cm(2) and 0.86-1.56 V, respectively, and are better than the values found in the literature. The BLT capacitors did not show any significant fatigue up to 10(10) read/write switching cycles. (C) 2004 American Institute of Physics.